(untitled) (International journal of medical sciences, 2026)
The transition from adolescence to adulthood, often coinciding with university studies, is a critical period for the formation of psycho-physiological adaptive mechanisms. Academic stress is a pervasive factor that can disrupt this adaptation, leading to psychosomatic disorders. This article presents a cross-sectional study conducted at Andijan State Medical Institute. Using the IMRAD framework, the research investigates the correlation between perceived stress levels and somatic health indicators among 300 medical students. The study utilized the Cohen Perceived Stress Scale (PSS-10) and simultaneous monitoring of hemodynamic parameters and sleep quality. The results indicate a strong positive correlation between high stress scores and the prevalence of tension headaches, sleep disturbances, and subclinical hypertension. The study concludes that chronic academic stress acts as a catalyst for early somatic pathology in youth, necessitating the implementation of institutional psychological support programs.